Acthar Gel (repository corticotropin injection) for persistently active SLE: study design and baseline characteristics from a multicentre, randomised, double-blind, placebo-controlled trial - Richard A Furie; Anca D Askanase; Enxu Zhao; Julie Zhu; Erin Connolly-Strong (Lupus Science and Medicine)
Objective SLE is a chronic inflammatory autoimmune disease characterised by the excessive production of autoantibodies, immune complexes and proinflammatory cytokines. Repository corticotropin injection (RCI) is a naturally sourced complex mixture of adrenocorticotropic hormone analogues and other pituitary peptides. RCI is approved by the US Food and Drug Administration for use during an exacerbation or as maintenance therapy in select cases of SLE. This paper discusses the design and baseline characteristics of a multicentre, double-blind, randomised, placebo-controlled, 24-week clinical trial evaluating the effect of RCI in reducing disease activity for patients with persistently active SLE despite moderate-dose corticosteroid use.Methods Efficacy will be evaluated using the SLE Responder Index-4 (SRI-4), SLE Disease Activity Index-2000 (SLEDAI-2K), British Isles Lupus Assessment Group-2004 (BILAG-2004) and Physician’s Global Assessment (PGA). The primary efficacy endpoint will be the proportion of SRI-4 responders at week 16. Secondary and exploratory endpoints will include changes in disease activity scores over time, prednisone dose and biomarkers of inflammation and bone turnover. The safety and tolerability profile of RCI will also be evaluated through adverse event profiles, physical examination, clinical laboratory tests and serum cortisol levels.Results Target enrolment for this global study is 270 patients, and as of 15 November 2019, the modified intent-to-treat population included 169 patients. The study cohort had 91.7% women, had a mean age of 39.7 years, mean SLEDAI-2K total score of 9.9, mean BILAG-2004 total score of 18.1, mean PGA of 59.7 and mean prednisone or equivalent daily dose of 11.1 mg. A total of 79.3% and 64.5% of patients were receiving concomitant antimalarial or immunosuppressive therapy, respectively.Conclusions Data from this study will provide valuable insights into the therapeutic role of RCI in refractory SLE, as well as important information regarding its safety profile.